Design Development Work Sheet Transformation Geometry Based on Van Hiele Geogebra Assisted to Improve the Understanding of The Student Concept - Susanti, Dewi; Suparman, S (Universitas Muhammadiyah Surakarta, 2018)
Understanding concepts is an important element in learning mathematics since the first until now the 21st century all-student math scores lowin terms of five aspects of mathematical ability is the ability of mathematical problem solving, mathematical communication, mathematical reasoning, understanding of mathematical concepts and connections. Students who has no understanding of the concept will be difficulties in taking the matterfurther, it is difficult to apply the concept in everyday life and not be able to develop the potential within themselves. This research has two objectives. First, this study is to analyze the needs of student worksheets on transformation geometry courses that need to be developed. Second, this study was designed to design student worksheets based on Van Hiele geometry transformation GeoGebra assisted which can improve understanding of concepts. This research is a model using a 4D model consists of four phases: define, design, develope, and dessiminate. The subjects of this study were lecturers and students of mathematics education. The collection instrument uses the validation , questionnaire and test sheets. Validation sheets are given to experts to get criticisms and suggestions related to worksheets. Questionnaires given to professors and great students to obtain comments and suggestions related to the response to the worksheet. Concept understanding tests are given to students to find out the effectiveness of worksheets. Data analyzed is using descriptive analysis. This study provides the results of the need for the development of technology-assisted student worksheets in the 21st century. This study concludes that the development of Van Hiele-based transformation geometry worksheets assisted by GeoGebra to improve students’ understanding of concepts needs to be developed.